Combination therapy of Ifenprodil with Piroxicam may be an effective therapeutic intervention in cerebral stroke: A hypothesis - Bhattacharya P.; Pandey A.K.; Paul S.; Patnaik R. (My University, 2025)
Owing to the intricate and multifaceted pathology of cerebral stroke, multiple drug therapy had long been suggested for effective stroke treatment. Therefore, the development of a potential new combination of drug is necessitated which can bring about desirable improved neuroprotection targeting different pathways against ischemic stroke. In this context, we hypothesize the combination effect of Piroxicam, a Non steroidal anti inflammatory drug with Ifenprodil, a NR2b selective NMDAR antagonist in animal model of cerebral ischemia. A few past studies have enumerated the neuroprotective roles of Piroxicam and Ifenprodil administered in singlet against cerebral ischemia in animal model, hence we hypothesized that by using Piroxicam and Ifenprodil in combination would provide additive neuroprotection than either of the agents used alone. In this article, we discuss our hypothesis regarding the possibility of Piroxicam and Ifenprodil as a potent combination which may have a positive therapeutic role in treatment of cerebral ischemia through its anti-inflammatory, anti-apoptotic and anti-oxidative characteristics of Piroxicam with Ifenprodil which has been proved to have neuroprotective, anticonvulsant and antinociceptive effects and has potentials for the treatment of several neuropsychiatric disorders, such as Parkinson's disease alcoholism and drug addiction. © 2012 Elsevier Ltd.